Will mHealth Revolutionize Health and Clinical Management and Open up New Horizons for Mental Health? - Conchon, E.; Bricon-Souf, N.; Section Editors for the IMIA Yearbook Section on Health and Clinical Management (Yearbook of Medical Informatics, 2016)
Objectives: To summarize recent research and emerging trends in the field of Health and Clinical management and propose a selection of best papers for year 2015.Methods: A literature review has been conducted by the two section editors and computerized provider order entry systems from bibliographic databases regards to health clinical management. As a result, a list of 15 candidate papers has been elaborated and a peer-reviewed has been performed by external reviewers. A consensus meeting has been organized between the two section editors and the editorial board to conclude the selection of the 3 best papers.Results: Starting with 1803 papers published in 2015, the full selection process ended with three papers from international peer-reviewed journals for the Health and Clinical Management section.Conclusion: IoT and Cloudification have a direct impact on health and clinical management this year. Telepsychiatry benefits directly from this development and take advantages of the improvement of smart homes and of the generalization of mHealth solutions. Social networks are starting to be integrated as valuable source of information that are complementary to clinical data for reasoning-based solutions.
Keywords: Health and Clinical Management; patient care management; medical record systems; technologies in healthcare; telemedicine